Reviews - Anne E. Mullin; Keith Rhodes; Ellen Davis; Jean R. Trounstine (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
Reviews Anne E. Mullin. Teaching Writing Creatively. (David Starkey, Ed., 1998). Keith Rhodes. Zen in the Art of Rhetoric: An Inquiry into Coherence. (Mark Lawrence McPhail, 1996). Ellen Davis. Women in Praise of the Sacred: 43 Centuries of Spiritual Poetry by Women. (Jane Hirshfield, Ed., 1994). Jean R. Trounstine. Educational Drama and Language Arts: What Research Shows. (Betty Jane Wagner, 1998).